Approach and Avoidance Sexual Goals in Couples with Provoked Vestibulodynia: Associations with Sexual, Relational, and Psychological Well‐Being. (1st August 2015) - Rosen, Natalie O.; Muise, Amy; Bergeron, Sophie; Impett, Emily A.; Boudreau, Gillian K.
ABSTRACT: Introduction: Provoked vestibulodynia (PVD) is a prevalent vulvovaginal pain condition that is triggered primarily during sexual intercourse. PVD adversely impacts women's and their partners' sexual relationship and psychological well‐being. Over 80% of women with PVD continue to have intercourse, possibly because of sexual goals that include wanting to pursue desirable outcomes (i.e., approach goals; such as a desire to maintain intimacy) and avoid negative outcomes (i.e., avoidance goals; such as avoiding a partner's disappointment). Aim: The aim of this study was to investigate associations between approach and avoidance sexual goals and women's pain, as well as the sexual, relational, and psychological well‐being of affected couples. Methods: Women with PVD (N = 107) and their partners completed measures of sexual goals, sexual satisfaction, relationship satisfaction, and depression. Women also completed measures of pain during intercourse and sexual functioning. Main Outcome Measures: (1) Global Measure of Sexual Satisfaction Scale, (2) Dyadic Adjustment Scale—Revised or the Couple Satisfaction Index, (3) Beck Depression Inventory‐II, (4) numerical rating scale of pain during intercourse, and (5) Female Sexual Function Index. Results: When women reported higher avoidance sexual goals, they reported lower sexual and relationship satisfaction, and higher levels of depressive symptoms. In addition, when partners of women reported higher avoidance sexual goals, they reported lower relationship satisfaction. When women reported higher approach sexual goals, they also reported higher sexual and relationship satisfaction. Conclusions: Targeting approach and avoidance sexual goals could enhance the quality and efficacy of psychological couple interventions for women with PVD and their partners.